Highly Stable Contact Doping in Organic Field Effect Transistors by Dopant‐Blockade Method - Kim, Youngrok (Adv Funct Mater, 2020)
In organic device applications, a high contact resistance between metal electrodes and organic semiconductors prevents an efficient charge injection and extraction, which fundamentally limits the device performance. Recently, various contact doping methods have been reported as an effective way to resolve the contact resistance problem. However, the contact doping has not been explored extensively in organic field effect transistors (OFETs) due to dopant diffusion problem, which significantly degrades the device stability by damaging the ON/OFF switching performance. Here, the stability of a contact doping method is improved by incorporating “dopant‐blockade molecules” in the poly(2,5‐bis(3‐hexadecylthiophen‐2‐yl)thieno[3,2‐b]thiophene) (PBTTT) film in order to suppress the diffusion of the dopant molecules. By carefully selecting the dopant‐blockade molecules for effectively blocking the dopant diffusion paths, the ON/OFF ratio of PBTTT OFETs can be maintained over 2 months. This work will maximize the potential of OFETs by employing the contact doping method as a promising route toward resolving the contact resistance problem.